'There is nowhere to take the child': a qualitative study of community members' views on managing early childhood substance use in Mbale, Uganda - V. Skylstad; I. M. S. Engebretsen; S. J. Nalugya; C. Opesen; G. Ndeezi; E. S. Okello; K. M. Moland; J. K. Tumwine; A. M. S. Skar (BMC, 2022)
Abstract Background Harmful alcohol use by 5-8-year-old children has been identified in Mbale District, Uganda. To further examine this finding, the present study explores the experiences and perceptions of community members regarding how childhood substance use (before age 10) is managed in this area. Methods We conducted eight focus group discussions with 48 parents of children aged < 10 years and 26 key informant interviews with teachers, health workers, child protection workers, police, local stakeholders, brewers, and others. Thematic content analysis was performed. Results Three main themes were identified: 'We don't talk about it': Despite concern, childhood substance use was not addressed in the community. Participants attributed this to three main factors related to a lack of leadership in addressing it, changing acceptability for peer parental interference, and uncertainty about repercussions related to children's rights. 'There is nowhere to take the child': Schools, police, and remand homes were intuitively considered appropriate arenas for managing childhood substance use but were considered inaccessible, unresponsive, and inadequate due to insufficient resources, competence, and training. Since substance use was not considered a medical problem, help from the health sector was only sought for adverse consequences, such as injury. This left the participants with the experience that there was in effect nowhere to take the child. 'The government has not done so much': The participants called for government action and clear laws that would regulate the availability of alcohol and other substances to children, but they had limited trust in the capacity and commitment of the government to act. Conclusions The participants were concerned about childhood alcohol and substance use, but the complexity and magnitude of the problem left them feeling incapacitated in responding. Relevant factors were identified on the community, institutional, and the government level, such as a lack of leadership in addressing it, a loss of mandate to interfere in child-rearing, inadequate services, weak legal structures, and missing government action. A strengthening of collective agency and public policy is necessary to prevent and address childhood alcohol and substance use.